حقوق کی درجہ بندی اور اسلامی قانون میں ان کی منتقلی: The Catergories of Rights and their transfer in Islamic Law - Dr. Samia Maqbool Niazi (MEI, 2023)
Intellectual Property Rights have never been as critical for economic development and growth as they are today. “These rights confer a bundle of exclusive rights in relation to the particular form or manner in which ideas are expressed or manifested, and not in relation to the ideas or concepts themselves. Thus, IP denotes the specific legal rights which authors and other IP holders may hold and exercise and not the intellectual property itself. In the corporate world, almost every development revolves around Intellectual property and the value associated with it. The Muslim world is lagging behind in the theoretical conviction about the legality or illegality of these rights and is, thus, failing to contribute to the growing developments in the field and their corresponding underlying concepts. This is leading to a lack of participation in a field that is rapidly assuming the position of the most prized possession of human beings.